VIOLENCE AGAINST THE SERBS OF GNJILAN KAZA 1900–1903 (Heritage, 2022)
According to the administrative reform of the Ottoman Empire at the end of the 19th century, the Gnjilan kaza was part of the Priština sandžak of the Kosovo vilayet. Kaza and the town of Gnjilane were of great importance for the Serbian population, which was compact and numerous in that area. It was precisely because of this that it was exposed to various atrocities and violence, which, according to Albanians idea, should have resulted in the emigration and reduction of the number of Serbs. Over time, Albanian crimes against Serbs in Old Serbia increased - it was recorded that there were 979 of them in the Gnjilan kaza from 1889 to 1912, of which 151 were for the period from 1900 to 1903.Violence in Gjilan kaza was repeated every day, and Serbs, faced with confiscation of property, burning of houses, rape of girls and women, ban on carrying weapons, were forced to emigrate to Serbia or other places in the Ottoman Empire. The Turkish authorities did not take measures to restore order and protect the Serbian population. Failure to take measures and impunity against the perpetrators had the effect of increasing the number of atrocities, which encouraged lesser-known perpetrators, even the smallest and most ordinary Albanians, to continue destroying Serbs in full view of the authorities, not only in Gnjilan kaza, but in the whole of Old Serbia.There are numerous cases where the authorities looked favorably upon the rioters and cooperated with them on an almost daily basis. From time to time, the military actions undertaken did not bring the expected results, and the situation on the ground, after the suspension of the actions of the army and the gendarmerie, returned to its original state, after which an even greater anarchy reigned. From the Gnjilan kaza, and in general from the Priština sandjak, it spread and covered other parts of the Kosovo vilayet. The actions of the Turkish authorities, in this case the kaymakam of Gnjilan, who not only did not react to the complaints of the Serbs, but often stood in solidarity with the wrongdoers and supported such actions, went hand in hand with Abanian's misdeeds.The consuls of the Kingdom of Serbia in Priština reported daily to the Government in Belgrade about the situation in Gnjilan kaza and Old Serbia in general, which through its representatives in the Ottoman Empire and in the capitals of the great powers tried to influence European opinion and cause their reaction.The Ottoman authorities wanted to demonstrate to Europe that they were interested in bringing order to Old Serbia, so the general inspector for the Rumelian vilayets, Hilmi Pasha, took some measures. However, his work was concentrated only on certain parts, but not on those where there was a need.
Keywords: Serbs, Albanians, Gnjilan kaza, Turkish authorities, violence, misdeed